Intracranial pressure, lateral sinus patency, and jugular ultrasound hemodynamics in patients with venous pulsatile tinnitus - Gao, Xiuli; Hsieh, Yue-Lin; Wang, Shenjiang; Shi, Suming; Wang, Wuqing (Frontiers in Neurology, 2022)
The clinical and hemodynamic characteristics of venous pulsatile tinnitus (PT) patients with normal or elevated cerebrospinal fluid pressure (CSFP) have not been clearly differentiated. This study aimed to explore CSFP among patients with PT as the solitary symptom, as well as quantitatively and qualitatively assess the role of the degree of transverse sinus (TS) stenosis and jugular hemodynamics in venous PT patients. A total of 50 subjects with venous PT with or without sigmoid sinus wall anomalies (SSWAs) were enrolled in this study. In addition to radiologic assessments for TS stenosis and invagination of arachnoid granulation (AG) in TS, CSFP and jugular hemodynamics were measured via cerebrospinal fluid (CSF) manometry and Doppler ultrasound. Apart from group comparisons and correlation analyses, multivariate linear regression, and receiver operating characteristic (ROC) models were used to identify the sensitivity and specificity of the index of transverse sinus stenosis (ITSS) and hemodynamic variables with inferential significance. The mean CSFP of all cases was 199.5 ± 52.7 mmH2O, with no statistical difference in CSFP between the diverticulum and dehiscence groups. Multivariate linear regression analysis demonstrated that CSFP was linearly correlated with ITSS and pulsatility index (PI). ROC analysis showed that the area under the ROC curve of PI was 0.693 at 200 mmH2O threshold, and the best PI cut-off value was 0.467, with a sensitivity of 65.7% and specificity of 81.8%. For 250 mmH2O threshold, the area under the ROC curve of PI was 0.718, and the best PI cut-off value was 0.467 with a sensitivity of 68.4% and specificity of 75.0%. Additionally, the area under the ROC curve of ITSS was 0.757, and the best ITSS cutoff value was 8.5 (p = 0.002, 95% CI = 0.616–0.898) with a sensitivity of 72.4% and specificity of 75.0% at 200 mmH2O threshold. In conclusion, patients with venous PT as the only presenting symptom should be suspected of having borderline or increased CSFP when they present with high ITSS, BMI and low PI. Further, AG in TS without encephalocele and empty sellae are not limiting findings for differentiating the level of CSFP in patients with venous PT.